Lockdown Changed Us in Turkey Eating Behaviors, Depression Levels, and Body Weight Changes During Lockdown - BİÇER, NİHAN ÇAKIR; Baş, Murat; Köse, Gizem; Duru, Pırıl Şenol; Baş, Dilşat; Karaca, Esen; Köseoğlu, Selen (Mattioli 1885, 2021)
Nationwide lockdown is a proven strategy to decrease inter-human transmission of the COVID-19. Prolonged home stay may be associated with some potential side effects as weight gain, depression, physical inactivity, unbalanced diet, and behavioral addiction disorders. During March-May of the social lockdown, Turkish adults (n:2955) completed an online sociodemographic form, Beck Depression Inventory (BDI) and Three Factor Eating Questionnaire (TFEQ)-21. During lockdown, 51.1% of the participants gained weight and TFEQ-21, emotional and uncontrolled eating scores were increased (p<0.001). Analysis showed that incraese in body weight was significantly related to the TFEQ-21 score, depression level, having a disease, decreased exercise, increased alcohol consumption, dismissal from work and reduced smoking (p<0.001). There were significant changes in uncontrolled and emotional eating, and cognitive restriction during the lockdown period. Additionally, changes in eating habits and physical activity may influence weight gain.
Keywords: Covid-19; Pandemic; Lockdown; Body Weight Management; Eating Behaviors; Depression